Two shape parametrizations for structural optimization of triangular shells. (1st April 2016) - Marino, Enzo; Salvatori, Luca; Orlando, Maurizio; Borri, Claudio
Highlights: Two shape parametrizations are proposed for the optimization of triangular shells. A Bézier surface and ad-hoc heuristic functions are used. The proposed optimization procedure leads to a strain energy reduction up to 88%. Abstract: The complexity of state-of-the-art tools for shell optimization may limit their applicability in common practice. We propose two shape parametrizations, inserted into a robust and simple procedure, based on linear finite elements and gradient-based optimization. We represent the mid-surface by triangular Bézier surface and ad-hoc heuristic functions. The first method allows searching for a general shape, while in the second one the functions are chosen according to structural and aesthetical criteria. Small number of design variables ensures efficiency. The procedure is applied to Kresge auditorium at MIT. Both parametrizations provide satisfactory results, with slightly better performances of Bézier surface representation.